Hadits Tasyabbuh Menurut Ulama Kontemporer: Penambahan Wawasan atas Penelitian Patel - Ramadhani, Miftahul; Fansuri, Fuad; Khotim, Khusnul (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2022)
The hadith prohibiting tasyabbuh has a wide range of interpretations, from the limits of tasyabbuh to the implications for the perpetrator. Patel has captured this diversity of interpretations among classical scholars, focusing primarily on Ibn Taymiyya and Najm al-Dīn al-Ghazzī. Due to the limitations of Patel's medieval research, this study aims to complement Patel's research by adding the views of contemporary scholars. The method used in this research is descriptive-analytical. The research steps taken are by describing the results of Patel's research first and then adding interpretations from contemporary scholars. Furthermore, the study focused on the interpretation of 'Abdullah Ibn Thāliḥ al-Fauzān because he more comprehensively explained the hadith of tasyabbuh. The study found that the interpretations of contemporary scholars still seem to follow those of the classical scholars who considered that one's appearance has major theological implications. Al-Fauzān is of the same opinion as other contemporary scholars. However, he adds the need for a more detailed ruling on tasyabbuh in a society that has been affected by globalization, because the social circumstances of today are different from those of the past, which were full of identity. He details the ruling of tasyabbuh from permissible to forbidden, and opens up ijtihad space for future possibilities. This research broadens the interpretative horizons of the Hadith on tasyabbuh, which has the potential to have wild interpretations when viewed only textually. This research only compiles the various interpretations of Middle Eastern scholars and no particular approach is used.